Assessing the Effects of Climate Policy on Companies' Greenhouse Gas Emissions - Ana Maria Montoya Gómez; Markus Zimmer (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the effect of climate policy on companies' greenhouse gas emissions using emissions data for the headquarters and subsidiaries of the world's biggest manufacturing, energy, and utility companies. Our results suggest that financial incentives and legal requirements to audit energy use reduce companies' emissions, whereas support schemes aimed at promoting the combined generation of heat and power increased emissions of non-utility companies and feed-in tariffs aimed at increasing the use of renewable energy sources for electricity generation increase emissions of utility companies. We also find loans and subsidies for energy efficiency improvements to increase emissions in the short term. In addition, our results provide a solid foundation for researchers seeking consistent and comparable estimates on the mitigation effects of typical climate policy instruments in a cross-country setting.
Keywords: H23; H32; Q42; Q48; Q54; Q58; 330; climate policy evaluation; greenhouse gas emissions; cross-country micro panel data; companies; firms